Thyroid storm complicated by multisystem organ failure requiring plasmapheresis to bridge to thyroidectomy: A case report and literature review. Issue 4 (2019) - Soomro, Rabail; Campbell, Natasha; Campbell, Stuart; Lesniak, Christopher; Sullivan, Michael; Ong, Raquel; Cheng, Jennifer; Hossain, Mohammad A
No abstract available